Decomposition analysis of efficiency and productivity of Malaysian manufacturing industry - Hassan, Azman (2012)
This study investigates the total factor productivity growth (TFPG) in Malaysia manufacturing industries over the period 1981 to 2006. The study period is divided into four sub-periods; pre-IMP 1981-1985, IMP 1986-1996, financial crisis 1997-1999, and post financial crisis 2000-2006. Analysis of the data involves two stages using the Stochastic Frontier Approach (SFA). The first stage involves the specification and estimation of the stochastic production function, followed by the tests for the specification of stochastic production functions. In the second stage, the selected specification of a regression model was used to predict technical efficiency effects. The sources of TFPG were decomposed into four components; technological progress (TP), technical efficiency (TE), scales effect (SC), and allocative efficiency (AE). The average technical efficiency estimates at the 2-Digit level for the period 1981-1991 for all sectors was 0.7381. The highest estimate was the Food, Beverages and Tobacco (31) sector at 0.9107 and the lowest was the Wood Products and Furniture (33) sector at 0.6398. For the period 2000-2006 the technical efficiency was 0.9454. The Pottery, China and Earthenware, Glass, and Non-metallic Mineral Products (36) sector ranked highest at 0.9684 while the Iron and Steel, and Non-Ferrous Basic Industries (37) sector was the lowest at 0.8639. The average growth rate of TP for all sectors for periods 1982-1985, 1986-1996,1997-1999, 1982-1999 and 2000-2006 were estimated at 0.0159, 0.0145, -0.0048,0.015 and -0.0110 respectively. The data shows decreasing TP over the years. The highest computed average growth rate of technical efficiency (TE) was 0.0023 for periods 1982-1985 and 1986-1996 and the lowest in 1997-1999 at 0.0022. TE increased from 0.0023 to 0.0032 for periods 1982-1999 and 2000-2006. This implies that the output constitute 0.32% of the potential output given by the best performance of the industries. For periods 1982-1985, 1986-1996, 1997-1999, the estimated average growth rate of SC were 0.0066, 0.0057, and 0.0001 respectively. For periods1989 -1999 and 2000-2006, SC estimated at 0.0029 and 0.0017. For period 1982-1985, the average growth rate of AE were estimated at -0.0063 and declined to -0.0070 during 1986-1996 and reached -0.0209 in 1997-1999. AE were estimated at -0.0142 during 1982-1999 and increased to 0.0158 for 2000-2006 periods. For periods 1982-1985, 1986-1996, and 1997-1999, the average growth rate of TFP was 0.0185, 0.0155, and 0.0234 respectively. TFP for 1982-1999 and 2000- 2006 was 0.0067 and 0.0096 respectively. From the results, we can infer that the average growth in TFP was driven mainly by TP which has positive impact until the period of Asian financial crisis. Changes in TE and SC had a significant positive effect, while AE had a negative effect from year 1982 to 1999. Increases in TFPG for all the sectors are minimally or is negative for the 2000-2006 which was adversely affected by deteriorating TP. The average growth rate of AE contributes the most compare to the other components TP, TE, and SC in the same period. The policymakers can recommend better suited policies that improve the productivity of Malaysian manufacturing sector only if they understand the sources of variation in productivity growth. The proposed decomposition enables policymakers to trace lagging productivity to particular component and to target those that boost productivity. Among some of the policies that can be derived from all of the decomposition of TFPG are research and development (R&D) on improving TP, greater access to foreign market to exploit potential SC, managerial practices on improving TE as well as less government intervention on improving AE.